On the reproducibility of spray-coated ZnO thin-film transistors - Lima, Guilherme R. [UNESP]; Braga, Joao P. [UNESP]; Gozzi, Giovani [UNESP]; Fugikawa-Santos, Lucas [UNESP] (Cambridge Univ Press, 2020)
Recent studies have shown spray-pyrolysis is a low-cost, simple and efficient technique for deposition of metal oxide semiconductors (such as zinc oxide) as the active layer of thin-film transistors (TFTs). However, to allow the translation from laboratory scale to industry the reproducibility of such method needs to be evaluated. We present herein a representative study concerning the reproducibility and uniformity of spray-coated ZnO TFTs using several devices, from different production batches, following the same fabrication protocol. We demonstrate that it is possible to obtain transistors with high performance and reproducibility by controlling the most relevant deposition factors, corroborated by a low deviation rate (below 10%) from the characteristic TFT parameters (mobility in saturation, threshold voltage and on/off ratio), which is compatible to commonly available commercial electronic devices.
Keywords: thin film; spray pyrolysis; solution deposition; semiconducting